A generalized inversion formula for the continuous Jacobi transform - Ahmed I. Zayed (International Journal of Mathematics and Mathematical Sciences)
In this paper we extend the definition of the continuous Jacobi transform to a class of generalized functions and obtain a generalized inversion formula for it. As a by-product of our technique we obtain a necessary and sufficient condition for an analytic function F(λ) in Reλ>0 to be the continuous Jacobi transform of a generalized function.